Back to the Future of Dental Education - Patricia A Reynolds (University of Zagreb. School of Dental Medicine, 2014)
Our students are like beacons, a bright light on the horizon, but with some way to go. Our educational methods that bring them safely into harbour have seen the test of time, but do we allow them enough freedom and creativity to sail their boats in the climate change of the digital era? Our students are chosen because they are smart and capable and we hope will bring credit to our institutions, but do we maximize their potential educationally? We need to go back to the future to begin to consider this.